EFEK MODERASI TATA KELOLA PERUSAHAAN ATAS PENGARUH TANGGUNG JAWAB SOSIAL KORPORAT TERHADAP KINERJA KEUANGAN - Adanan Silaban; Meilinda Stefani Harefa (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
This study aims to determine the effect of the interaction of good corporategovernance (GCG) with corporate social responsibility (CSR) on financialperformance (ROA). The population of this study are banking companies listed onthe Indonesia Stock Exchange in the 2011-2018 research year and listed in theCorporate Governance Perception Index (CGPI), totaling 11 companies. Themethod of determining the sample by purposive sampling method, with severalpredetermined criteria, the number of observations is as many as 88 bankingcompanies Tbk. The variables used in this study are ROA as the dependentvariable, CSR and GCG as independent variables, while placing GCG as amoderating variable. This study uses multiple linear regression analysis for thehypothesis and multiple linear regression analysis with Moderated RegressionAnalysis (MRA) test to test the effect of interaction. The results of this studyindicate that partially and simultaneously CSR and ROA have a positive andsignificant effect on financial performance, and the effect of GCG interaction onCSR strengthens the influence of CSR on financial performance.